Shakespeare and Nezami : A study of gender roles and gender reversals in Romeo and Juliet and Layli and Majnoon - Daram, Dr. Mahmoud Ghoreishi, Marziyeh S; M. Suheyl Umar (Lahore Iqbal Academy Pakistan, 2013)
A comparative study of these iconic writers is therefore a much-needed addition to our knowledge of ourselves, and of the world we live in.
Include Bibliography